Monitorização Intraoperatória com Ecocardiografia Transesofágica em Cirurgia Cardíaca - Júnior, Carlos Galhardo; Botelho, Eduardo Souza Leal; Diego, Luis Antonio dos Santos [UNESP] (Elsevier, 2011)
Background and objectives: Since its clinical introduction in the 80s, intraoperative transesophageal echocardiography (TEE) has represented one of the greatest advances in modern cardiac anesthesia. It is a semi-invasive technique that allows direct and fast visualization of structural anatomy of the heart and great vessels as well as contributes to hemodynamic and functional evaluation of the cardiovascular system. Thus, it has become an important monitor in aiding the diagnosis of cardiac pathologies and anesthesia and surgical interventions. The objective of this report was to perform a comprehensive review on the use of intraoperative TEE in cardiac surgery. Contents: This article reviews some aspects of ultrasound physics, imaging techniques, echocardiographic cuts used more oftenly, indications, and main clinical applications in addition to contraindications and complications. Conclusions: Intraoperative TEE is a safe method of cardiovascular monitoring, which is useful in the formulation of a surgical strategy, orientation of hemodynamic interventions, and immediate assessment of surgical outcomes. Once qualified to use the method, the anesthesiologist expands its role in perioperative medicine, providing clinical information necessary to the anesthetic-surgical procedure in cardiac surgery. © 2011 Elsevier Editora Ltda.
Intraoperative Monitoring with Transesophageal Echocardiography in Cardiac Surgery
Keywords: Cardiac surgical procedures; Echocardiography, transesophageal; Intraoperative care